Management of PJJ-Based Social Studies Learning Activities During the Covid-19 Pandemic at Setia Bhakti Cilawu Middle School, Garut Regency - Nanan Jujum, Nanan Jujum; Slamet Nopharipaldi Rohman; Triani Widyanti (Institut Pendidikan Indonesia, 2024)
Management of teaching and learning activities is an effort made by the teacher so that the learning process can run well and smoothly. The success of the teacher in carrying out teaching and learning activities is inseparable from how the teacher manages the learning carried out so that students can achieve optimal levels of ability in accordance with the expected goals. Management of teaching and learning is an important element of teacher competence and must be implemented. Because the management of teaching and learning is needed in learning activities. The purpose of this study is to identify that in carrying out innovative learning in order to ensure how learning activities continue, even though students are at home. The research method used qualitative method with qualitative descriptive type, data collection techniques by observation, interviews and documentation studies. The results of the study show that the way to overcome the obstacles experienced during the process of implementing distance learning at Setia Bhakti Cilawu Middle School is that the teacher independently records learning videos about material that is difficult to understand, parents re-study the material so that they can help students in learning, the teacher gives project assignments so students can be creative in making media, and establish good communication between parents and teacher.